Pengaruh Variasi Suhu Di Slaker I-V Terhadap Variasi Total Active Alkali White Liquor Di Unit Recausticizing Plant PT. RAPP - Hutagalung, Maha Putra; Fermi, M. Iwan; Rionaldo, Hari; Siregar, Dompak M. (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The Kraft pulping process has become the most widely used pulping process in the papermaking industry since its discovery in 1879.This process has three main advantages over other pulping processes, namely the resulting fiber is stronger, can be applied to all wood species. Both softwood and hardwood, and lower operating costs due to the chemical can be reprocessed at a high efficiency of around 97%. One of the units in chemical reprocessing is a plant that aims to produce white liquid (WL) from green liquid (GL) which is then used as a medium for cooking chips in the Digester. This study aims to study temperature variations in the I-V slaker unit at PT. RAPP on the total active alkali (TAA) variation of WL in WL tanks. The temperature of each slaker was correlated with TAA WL using a linear regression approach and was re-tested by comparing the causticizing efficiency in each slaker. To get the optimal operational process in each slaker for the variation of TTA GL and temperature in the slaker, the multiple regression method approach was used. The TAA WL prediction results from multiple regression between TTA and temperature in the slaker were then compared with the TAA WL obtained in the laboratory and it was found that the two values were very close. So this method can be used to determine the optimal operation for variations in TTA GL and temperature in the slaker. If the variation of TAA WL is very small, the proportion of alkaline charge used in the digester can be so that the operational costs can be drawn. Keywords: Kraft Pulp, Slaker, Causticizing Efficiency, Green Liquor, Total active alkali, White Liquor